Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.153
|View full text |Cite
|
Sign up to set email alerts
|

Kirchhoff Index as a Measure of Edge Centrality in Weighted Networks: Nearly Linear Time Algorithms

Abstract: Estimating the relative importance of vertices and edges is a fundamental issue in the analysis of complex networks, and has found vast applications in various aspects, such as social networks, power grids, and biological networks. Most previous work focuses on metrics of vertex importance and methods for identifying powerful vertices, while related work for edges is much lesser, especially for weighted networks, due to the computational challenge. In this paper, we propose to use the well-known Kirchhoff inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The power of vertex or edge graph sparsifiers, which preserve certain properties while reducing problem sizes, has long been studied in data structures [20,21]. Ideas from these results are central to recent works on offline maintenance for 3-connectivity [57], generating random spanning trees [18], and new notions of centrality for networks [43]. Our result is the first to maintain such vertex sparsifiers, specifically Schur complements, for general graphs in online settings.…”
Section: Related Workmentioning
confidence: 82%
“…The power of vertex or edge graph sparsifiers, which preserve certain properties while reducing problem sizes, has long been studied in data structures [20,21]. Ideas from these results are central to recent works on offline maintenance for 3-connectivity [57], generating random spanning trees [18], and new notions of centrality for networks [43]. Our result is the first to maintain such vertex sparsifiers, specifically Schur complements, for general graphs in online settings.…”
Section: Related Workmentioning
confidence: 82%
“…Our investigation can be viewed as combining this line of current based centrality measures with the study of selecting groups of k vertices. For the former, a subset of the authors of this paper (Li and Zhang) recently demonstrated that current flow centrality measures for single edges can be computed provably efficiently [LZ18]. Our approximation algorithm in Section 7 is directly motivated by that routine.…”
Section: Related Workmentioning
confidence: 99%
“…Kirchhoff index has found wide applications. For example, it can be used as measures of the overall connectedness of a network [45], the robustness of first-order consensus algorithm in noisy networks [46], as well as the edge centrality of complex networks [47]. In recent years, several modifications for Kirchhoff index have been proposed, including additive degree-Kirchhoff index [48] and multiplicative degree-Kirchhoff index [40].…”
Section: Electrical Networkmentioning
confidence: 99%